2017
DOI: 10.1108/jibr-02-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Impulse buying intentions of young consumers from a hedonic shopping perspective

Abstract: Purpose The purpose of this research paper is to examine predictors of impulsive buying intentions among youngsters from a hedonic shopping perspective. Recent theoretical work suggests that impulsive buying can function as a form of different hedonic shopping value dimensions such as fun, social interactions, novelty, escapism and outside appreciation. Design/methodology/approach The present research empirically tests a theoretical model of impulse buying intentions by examining the associations between hed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 76 publications
4
59
0
9
Order By: Relevance
“…The results of this study are in accordance with the findings of some previous researchers (Dey & Srivastava, 2017;Kosyu, Hidayat, & Abdillah, 2014;Mardiati, 2015;Tambuwun, 2016). Kosyu, Hidayat, & Abdillah (2014) found significant effects of hedonic shopping motives on impulse buying.…”
Section: Hypothesis Testing Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study are in accordance with the findings of some previous researchers (Dey & Srivastava, 2017;Kosyu, Hidayat, & Abdillah, 2014;Mardiati, 2015;Tambuwun, 2016). Kosyu, Hidayat, & Abdillah (2014) found significant effects of hedonic shopping motives on impulse buying.…”
Section: Hypothesis Testing Resultssupporting
confidence: 93%
“…This is because when someone shops in a hedonic way, then (s)he will not consider the aspect of benefits so that the possibility of impulsive buying will also be higher. Dey & Srivastava (2017) found a positive influence of hedonic shopping motivation on impulse buying intentions. He also found the moderating influence of the variable of money availability and time availability.…”
Section: Hypothesis Testing Resultsmentioning
confidence: 91%
“…Thus, consumers who are concerned about their feelings (emotional worth) of enjoyment or fun while searching for hotels are willing to patronise green hotels. For example, a study by Dey and Srivastava (2017) found that indeed, a hedonistic buying value has a significant relationship to an impulse buying behaviour. Also, this finding is supported by Jaini et al (2019) as they found hedonistic buying values to influence pro-environmental values which subsequently influences consumers green purchase behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…These factors positively influence the impulse purchasing intentions. However, the situational factors such as money availability, time availability and task definition moderate the relationship between shopping values and impulse purchasing intentions (Dey & Srivastava, 2017). Further, it was also found that emotion of the customer, self-esteem and life satisfaction positively influence the impulse buying (Nayebzadesh & Jalaly, 2014).…”
Section: Impulse Buyingmentioning
confidence: 99%